Effects of Crude and Partially Purified Mannanase on the Fibre Content of Palm Kernal Cake/Expeller - Mustapha, Safarul (2011)
Palm Kernel Cake/Expeller (PKC/E) is an agricultural waste of palm oil mill which contributed about 2.2 million tones in 2007 in Malaysia. It is an important ingredient for the formulation of animal feed instead of corn and soybean husk. The PKC/E fibre composed mainly of galactomannan type of hemicelluloses, which can barely be consumed by non-ruminant (monogastric) animals. Mannanase is a major extracellular enzyme which is secreted to convert mannan into simple sugar of mannose. In this study, Aspergilus niger FTCC 5003, a mannanase producer and PKC/E as a sole carbon source were fermented in 500 mL shake flask using the optimised parameter conditions for 10 days and the culture broth were collected for hydrolysis purpose. Purification of the mannanase from submerged fermentation of PKC/E obtained from fermentation A. niger FTCC 5003 was also carried out. Crude and partially purified enzymes were employed in this study to degrade PKC/E using enzymatic hydrolysis technique to compare with fermented PKC/E. The characteristic of palm kernel cake under fermented and hydrolysed conditions were studied under Scanning Electron Microscope (SEM) and the Near Infrared System (NIR) was used to perform proximate analysis of quantitative parameter. SEM showed fermented PKC surface structure were significantly degraded compared with the hydrolyzed palm kernel. The results of Near infrared reflectance spectroscopy (NIRS) proved that the crude fiber (CF) of palm kernel cake was reduced by enzymatic hydrolysis. The ether extract (EE) or crude fat which contained fat soluble vitamin showed the highest in hydrolyzed palm kernel cake. Partial purification of mannanase enzyme, produced by A. niger FTCC 5003 was achieved by fractional precipitation with ammonium sulphate and Tangential Flow Filtration (TFF) ultrafiltration. The purification of mannanase collected from TFF ultrafiltration was achieved with 4.8 fold of purification and 32% recovery whereas the purification of mannanase precipitated by ammonium sulphate was achieved 9.89 fold of purification and 28% recovery. The molecular mass determinations of with partially purified mannanase were estimated as 32 kDa by SDS-PAGE. The optimal temperatures of the purified mannanase was 45°C and stable at 40-50°C, and the pH optimum was at pH 4-6. However, it was most stable at pH 3-7.